Holistic Evaluation of Field‐Scale Denitrifying Bioreactors as a Basis to Improve Environmental Sustainability. Issue 3 (1st May 2016) - Fenton, Owen; Healy, Mark G.; Brennan, Fiona P.; Thornton, Steven F.; Lanigan, Gary J.; Ibrahim, Tristan G.
Abstract : Denitrifying bioreactors convert nitrate‐nitrogen (NO3 –N) to di‐nitrogen and protect water quality. Herein, the performance of a pilot‐scale bioreactor (10 m long, 5 m wide, 2 m deep) containing seven alternating cells filled with either sandy loam soil or lodgepole pine woodchip and with a novel "zig‐zag" flow pattern was investigated. The influent water had an average NO3 –N concentration of 25 mg L −1 . The performance of the bioreactor was evaluated in two scenarios. In Scenario 1, only NO3 –N removal was evaluated; in Scenario 2, NO3 –N removal, ammonium‐N (NH4 –N), and dissolved reactive phosphorus (DRP) generation was considered. These data were used to generate a sustainability index (SI), which evaluated the overall performance taking these parameters into account. In Scenario 1, the bioreactor was a net reducer of contaminants, but it transformed into a net producer of contaminants in Scenario 2. Inquisition of the data using these scenarios meant that an optimum bioreactor design could be identified. This would involve reduction to two cells: a single sandy loam soil cell followed by a woodchip cell, which would remove NO3 –N and reduce greenhouse gas (GHG) emissions and DRP losses. An additional post‐bed chamber containing media to eliminate NH4 –N and surface capping to reduce GHG emissions further is advised. Scenario modeling, such as that proposed in this paper, should ideally include GHG in the SI, but because different countries have different emission targets, future work should concentrate on the development of geographically appropriate weightings to facilitate the incorporation of GHG into a SI. Core Ideas: Holistic assessment of pilot‐scale denitrifying bioreactors highlighted pollution swapping. A sustainability index across two scenarios identified net production or removal of pollutants. A detailed within‐bioreactor assessment identified the provenance of losses. Damage cost to the environment and human health assessment justified conversion to a new setup. This approach allows for a holistic assessment and improvement of a denitrifying bioreactor.